ANALISIS STRUKTUR RUMAH SAKIT DI JALAN SARWO EDHIE KOTA SEMARANG DENGAN SISTEM GANDA - Hani Purwanti; Muhammad Azis Arwidiansyah; Muhammad Alfian Rahmansyah; Talitha Zhafira (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2025)
Semarang City is an area that has the potential to experience earthquakes with a significant level of risk of building damage, including health facilities such as hospitals. This study aims to assess the structural performance of a Hospital in Semarang by combining two systems, namely special moment frames and shear walls. The evaluation was carried out through dynamic response spectrum analysis referring to SNI 1726:2019 by examining parameters such as mass participation, shear force distribution, inter-floor displacement, P-Delta effect, and dual system control. 3D modeling using ETABS v18.1.1 to calculate various loads, including dead load, live load, and earthquake load. According to SNI provisions, the study results revealed that mass participation exceeded 90% in mode 12. The maximum deviation between floors was recorded at 25.16 mm (X direction) and 17.24 mm (Y direction), within the safe limit of 48.46 mm. The P-Delta value (0.0149 and 0.0102) is also below θ maks, indicating structural stability. In conclusion, the design of this dual-system hospital meets the earthquake-resistant criteria and can be a reliable alternative for construction in earthquake-prone areas such as Semarang.